2017
DOI: 10.1371/journal.pone.0173897
|View full text |Cite
|
Sign up to set email alerts
|

Reverse lectin ELISA for detecting fucosylated forms of α1-acid glycoprotein associated with hepatocellular carcinoma

Abstract: Altered fucosylation of glycoproteins is associated with development of hepatocellular carcinoma (HCC). Lectins have been commonly used to assay changes in fucosylation of plasma glycoproteins. In the present study a recombinantly engineered form of the fucose binding lectin Aleuria aurantia (AAL) consisting of a single binding site for fucose (S2), was used to construct a reverse lectin ELISA method. Microtiter plates coated with the S2 lectin were used to capture glycoproteins from plasma samples followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…The sub-picomolar binding affinity of MVN to ManLAM and opportunistic bioconjugation framework made it an ideal capture reagent, while the ubiquitous use of antibodies as detection conjugates in ELISAs prompted the selection of Ab28 as the detection conjugate. 34,35 The capture bead was generated by loading streptavidin magnetic Dynabeads with biotinylated MVN. 21 An "all-in-one" OB-ELISA format was employed because it shortened overall assay time by 30+ minutes when compared to sequential addition without a significant impact on the signal-to-noise ratio (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sub-picomolar binding affinity of MVN to ManLAM and opportunistic bioconjugation framework made it an ideal capture reagent, while the ubiquitous use of antibodies as detection conjugates in ELISAs prompted the selection of Ab28 as the detection conjugate. 34,35 The capture bead was generated by loading streptavidin magnetic Dynabeads with biotinylated MVN. 21 An "all-in-one" OB-ELISA format was employed because it shortened overall assay time by 30+ minutes when compared to sequential addition without a significant impact on the signal-to-noise ratio (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Serum AGP is synthesized mainly by hepatocytes in the liver, with approximately 45% of molecular weight contributed by N -glycans 14 . Changes in serum AGP glycosylation are highly correlated with HCC progression 1921 ; however, it is unclear how N -glycan structures of AGP alter from liver cirrhosis to early HCC in different etiologies. In this study, we performed a comprehensive comparison of N -glycan structures of serum AGP between HCC and cirrhosis patients of the three common etiologies (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer-associated glycosylation aberrations provide a rationale for discovering new biomarkers using glycomic/glycoproteomic technologies 2328 . Previous studies revealed that although there was an increase in fucosylation level in both cirrhosis and HCC patients, HCC patients expressed AGP with more multifucosylated glycans 19,20 . Zhang et al .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A well‐known fucose‐binding lectin from the Orange peel fungus Aleuria aurantia (AAL), recently bioengineered as a monomeric form AAL‐S2 with high affinity towards α1–6 fucosylated (core‐fucosylated) glycans 32 was used to construct a reverse‐lectin ELISA method to support identification of aberrantly fucosylated alpha‐1 acid glycoprotein in the serum of HCC patients 33 . Immuno‐histochemical studies revealed its diagnostic potential by differentially binding to normal and metastatic cancerous tissues 34 .…”
Section: Discussionmentioning
confidence: 99%